The stylization of Sufism in the contemporary Algerian poetry ’’the fortune of my life ’’ by kadour rahmani as a model. - chanafi, Aissa (The Notebooks of the Algerian Poetics Laboratory Journal, 2021)
Abstract: Acquired contemporary Algerian poetic texts a richness artistic through the poets ’openness to the traditional references and their stylization and perhaps the most prominent of these sufi heritage ,wich greatly influenced their expressive styles and increased the aesthetics of the poem and depth of its contents. The poet kaddour rahmani invested this in refining his poetic